2009
DOI: 10.2220/biomedres.30.113
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of ENaCβ in the terminal Schwann cells associated with the periodontal Ruffini endings of the rat incisor

Abstract: Epithelial sodium channels (ENaCs) are a subfamily of ion channels within the degenerin/ENaC (DEG/ENaC) superfamily. Previous studies have shown the immunolocalization of ENaC in the neural elements of the cutaneous mechanoreceptors as well as dorsal root and trigeminal ganglion neurons, indicating the involvement of this molecule in mechanotransduction. The present study examined the expression of ENaCβ, a major component of ENaC protein, in the mechanoreceptive Ruffini endings in the periodontal ligament of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
(29 reference statements)
0
10
1
Order By: Relevance
“…It would be also interesting for future studies to investigate mechanically activated current in dissociate DRG neurons to characterize other mechanosensory phenotypes of ASIC TKO s. We have shown slower mean conduction velocity (CV) of Aδ-AMs from ASIC TKOs. Previous studies have demonstrated the expression of ASIC2 or other channels from DEG/ENaC superfamily by human or rat Schwann cells [56], [57]. Therefore, while the exact underlying mechanism remains unclear, warranting further investigation, this might suggest a possible role of ASIC s in Schwann cell function and axonal conduction in sub-populations of afferents.…”
Section: Discussionmentioning
confidence: 97%
“…It would be also interesting for future studies to investigate mechanically activated current in dissociate DRG neurons to characterize other mechanosensory phenotypes of ASIC TKO s. We have shown slower mean conduction velocity (CV) of Aδ-AMs from ASIC TKOs. Previous studies have demonstrated the expression of ASIC2 or other channels from DEG/ENaC superfamily by human or rat Schwann cells [56], [57]. Therefore, while the exact underlying mechanism remains unclear, warranting further investigation, this might suggest a possible role of ASIC s in Schwann cell function and axonal conduction in sub-populations of afferents.…”
Section: Discussionmentioning
confidence: 97%
“…This was an unexpected finding, but not surprising, since ASIC2 has been also detected in satellite cells of the rat DRG (Kawamata et al 2006), and in the inner core cells of the murine Pacinian corpuscles . Furthermore, the expression of other proteins from the ASICs family was also detected in the Schwannrelated cells present in rat Ruffini endings (Hitomi et al 2009). …”
Section: Independentlymentioning
confidence: 89%
“…ASIC2a and ASIC3 are expressed in mechanoreceptors, including specialized cutaneous mechanosensory structures like Merkel nerve endings, palisades of lanceolate nerve endings, Meissner corpuscles, and Pacinian corpuscles (Garcia-Añoveros et al 2001;Price et al 2000Price et al , 2001Montaño et al 2009). Other members of the Deg/ ENaC family, like b-ENaC and c-ENaC, were also detected in different kinds of mechanoreceptors Montaño et al 2009;Hitomi et al 2009). Interestingly, the expression of Deg/ENaC in Pacinian corpuscles is differentially regulated by BDNF and NT-4 acting through TrkB ).…”
mentioning
confidence: 99%
“…This implies that the blockade of ENaCs on the salt taste receptors of the tongue (Chandrashekar et al, 2010) were surely not a factor that can explain the c-Fos labeling in the AP. A similar argument can be advanced regarding the ENaCs associated with the trigeminal nerve or its branches that innervate the teeth (Fricke et al, 2000; Hitomi et al, 2009). The amount of c-Fos labeling that occurred in the spinal trigeminal nucleus in amiloride-treated rats never exceeded the number of activated cells observed in the control animals.…”
Section: Discussionmentioning
confidence: 75%